2017
DOI: 10.7150/jca.21141
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of Albumin-to-Globulin Ratio in Patients with solid tumors: A Systematic Review and Meta-analysis

Abstract: Background: Albumin and globulin are main components of serum protein. The level of albumin and globulin partially represents the nutrition status and immune system. Albumin-to-globulin ratio (AGR) has been reported as a prognostic factor in various cancers. We therefore performed a meta-analysis to elucidate the prognosis effect of AGR on survival outcomes in solid tumors.Method: Six electronic database were searched for the relevant articles that assessing the prognostic value of pre-treatment AGR in solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 47 publications
4
78
0
4
Order By: Relevance
“…We chose to use dichotomized cut-offs because previous studies utilizing such cut-offs have shown a better association between PLR and overall survival than those with three risk categories [ 23 ]. The optimal cut-off values in the present study, which were determined using a statistical method, were similar to those of the previous studies [ 26 29 ]. Nevertheless, they warrant further validation in large, prospective studies since outcome-oriented approach to select cut-off value might result in overfitting.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We chose to use dichotomized cut-offs because previous studies utilizing such cut-offs have shown a better association between PLR and overall survival than those with three risk categories [ 23 ]. The optimal cut-off values in the present study, which were determined using a statistical method, were similar to those of the previous studies [ 26 29 ]. Nevertheless, they warrant further validation in large, prospective studies since outcome-oriented approach to select cut-off value might result in overfitting.…”
Section: Discussionsupporting
confidence: 83%
“…Globulin plays an important role in immunity and inflammation. Because levels of both albumin and globulin are easily influenced by factors, such as dehydration or oedema, AGR has been suggested and explored as a prognostic factor in several cancers [ 26 ]. In the present study, the serum albumin levels and AGR were significantly associated with distant LN metastasis, which was the strongest independent predictive factor of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the present study, the AGR may be a more reliable predictor of outcomes inpatients, compared with the LNR. The reason for this may be that AGR may provide a true reflection of the condition of a patient that the AGR provides the combined information of immune and nutritional situation of patients (27,28). According to previous studies, AGR was considered to be closely associated with the patient immune system, and may be used as an indicator of the immune condition of patients in the future (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Ikan gabus dimanfaatkan dalam bidang kesehatan yang disebut sebagai medicinal freshwater fish, seperti digunakan untuk mempercepat proses penyembuhan luka pascaoperasi dan melahirkan (Rahayu et al, 2016). Ikan gabus memiliki manfaat biomedik yan g san gat mengu ntung kan, seperti antiradang, antijasad renik, antinyeri nosisepsi (nociception) dan sifat antikanker (Hue et al, 2017). Ikan gabus mengandung asam amino dan asam lemak dengan kadar yang tinggi dan memiliki kemampuan bagus dalam proses penyembuhan luka (Shafri dan Abdul, 2012).…”
Section: Pendahuluanunclassified
“…Firlianty et al (2014) menyatakan bahwa asam amino yang dikandung dalam daging ikan gabus di antaranya asam amino arginin (3,55%), valin (7,58%), isoleusin (5,36%), asam aspartat (16,09%), tirosin (1,99%), alanin (15,62%), dan tirosin (2,68%). Albumin yang dikandung dalam daging ikan gabus berperan penting dalam peredaran dan farmakodinamik obat antikanker (Hue et al, 2017). Albumin ikan gabus sangat baik digunakan untuk penderita hipoalbumin (rendah albumin), dan penyembuhan luka pascaoperasi dan luka bakar (Evi dan Ika, 2013).…”
Section: Pendahuluanunclassified